Information-protection Systems Estimation in Telecommunication Systems - Конахович, Г. Ф.; Голубничий, О. Г.; Пузиренко, О. Ю. (Problems of Informatization and Control, 2007)
An estimation of telecommunication systems security criterion on the basis of technical and economic features and factors of communication systems, attack realization systems, and in- formation-protection systems is proved. Wideband signals efficiency for confidential information transfer and protection is analyzed